The Effect Of Health Education Using Leaflet Media And Lecture Methods On Increasing Pregnant Women's Knowledge About Gestational Diabetes Mellitus In The Working Area Of The North Aceh District Community Health Center - Elizar, Elizar; Jasmiati, Jasmiati; Prihatin, Nova Sumaini; Yusnaini, Yusnaini; Pebryatie, Elit; Nurrochmi, Endang (Ann Publisher, 2025)
Background: Gestational diabetes mellitus (GDM) is a growing global health concern with increasing maternal-fetal morbidity and long-term health risks, and poor knowledge of GDM among pregnant women raises the potential for serious complications. Aim: This study aims to analyze the effect of health education using leaflets and lectures on pregnant women's knowledge about gestational diabetes mellitus in the community health center (Puskesmas) in North Aceh Regency. Methods. The study used a quasi-experimental design with a non-equivalent control group. The sample was drawn from pregnant women undergoing antenatal care at the community health center (Puskesmas) in North Aceh Regency, with a total of 64 respondents from the intervention and control groups. Respondents were selected using purposive sampling according to predetermined criteria. Results: The Wilcoxon signed-rank test showed a significant difference in knowledge before and after health education using lectures and leaflets on pregnant women's knowledge. Conclusions: Health education using lectures and leaflets has a greater impact on improving pregnant women's knowledge than lectures alone. Implications: Healthcare providers should develop health education programs that combine several simple and clear educational methods about gestational diabetes mellitus for pregnant women and their families.